Generalized Arithmetic Graphs With Equal and Unequal Powers of Annihilator Domination Number - Aparna, P.; Suryanarayana Rao, K. V.; Reddy, E. Keshava (Communications in Mathematics and Applications, 2021)
Current work is carried out in Generalized Arithmetic Graphs to explore the theory of conquest by the Annihilator Dominion Number of Upper bound. Kulli and Janakiram [8] first demonstrated split domination while Suryanarayana Rao and Vangipuram [12] introduced the domination of Annihilator and obtained several interesting results in Arithmetic graphs. There are few significant and important studies on Annihilator’s domination being examined in the current paper.